PEMERATAAN BEBAN PADA GARDU KD 056 PENYULANG TABANAN PT PLN (PERSERO) DISTRIBUSI BALI AREA BALI SELATAN - I Putu Agus Semara Putra; I Ketut Wijaya; I Made Mataram (Program Studi Teknik Elektro UNUD, 2018)
Load balancing is a routine done by PLN to manage a distribution substation. It is done on Peak Load Time (WBP) only. Initial load measurements and load data on a distribution transformer need to be done for balancing as input of simulation software. The load imbalance in a power distribution system is due to an imbalance in single phase loads in the R, S and T phases in low voltage networks due to the imbalance of the load the current in the neutral transformer arises. The current flowing in the neutral of the transformer causes losses, i.e. losses due to neutral currents in the neutral conductor of transformers and losses due to neutral currents flowing to the ground. In this research load equalization in substation KD 056 was done by making a simulation on the ETAP program by measuring the value of the voltage on the KD 056 substation. The result of load balancing in KD 056 substation with the simulation ETAP program i.e. the voltage drop obtained from the percentage of KD 056 substation after being balanced by voltage drop on phase R which decreased from 7.30% to 1.36% from the 219VA source voltage. Once the KD 056 substation is balanced, it can lower the voltage drop and power losses, thus the system voltage meets the standards of PLN.